Electrochemically Tunable Proton‐Coupled Electron Transfer in Pd‐Catalyzed Benzaldehyde Hydrogenation. Issue 4 (12th December 2019) - Koh, Katherine; Sanyal, Udishnu; Lee, Mal‐Soon; Cheng, Guanhua; Song, Miao; Glezakou, Vassiliki‐Alexandra; Liu, Yue; Li, Dongsheng; Rousseau, Roger; Gutiérrez, Oliver Y.; Karkamkar, Abhijeet; Derewinski, Miroslaw; et al.
Abstract: Acid functionalization of a carbon support allows to enhance the electrocatalytic activity of Pd to hydrogenate benzaldehyde to benzyl alcohol proportional to the concentration of Brønsted‐acid sites. In contrast, the hydrogenation rate is not affected when H2 is used as a reduction equivalent. The different responses to the catalyst properties are shown to be caused by differences in the hydrogenation mechanism between the electrochemical and the H2 ‐induced hydrogenation pathways. The enhancement of electrocatalytic reduction is realized by the participation of support‐generated hydronium ions in the proximity of the metal particles. Abstract : Pooled forces : A series of Pd/C catalysts with modified carbon supports were used for the electrochemical hydrogenation of benzaldehyde. The presence of acid groups at the metal–support interface enhances the catalytic activity of Pd due to the participation of Brønsted‐acid sites in the hydrogenation mechanism.